Sosialisasi Pencegahan Perundungan dan Kekerasan di Lingkungan Sekolah - Hardika Saputra (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
Bullying and violence in school environments are serious issues that affect student development. This study aims to conduct socialization on the prevention of bullying and violence at Al Qudwah Integrated Islamic Elementary School (SDIT) in Punggur, Central Lampung. The methods used in this study include interactive presentations, discussions, role-playing, and teacher training. The results show that the program successfully increased students' awareness of the dangers of bullying and provided them with skills to report acts of violence. Additionally, the establishment of new institutions such as a confidential reporting system and an anti-bullying team created a safer and more supportive school environment. The increased involvement of teachers in preventing bullying was also significantly observed, in line with social learning theory and social norms. This program is expected to continue to encourage a positive school culture free from violence.